Recensions (Apocrypha, 2014)
Kampen, James, Wisdom Literature, Grand Rapids, Michigan/ Cambridge, William B. Eerdmans, 2011Bovon, François, The Emergence of Christianity, Luke Drake (éd.) (Wissenschaftliche Untersuchungen zum Neuen Testament 319), Tübingen, Mohr Siebeck, 2013Aune, David E., Jesus, Gospel Tradition and Paul in the Context of Jewish and Greco-Roman Antiquity. Collected Essays II (Wissenschaftliche Untersuchungen zum Neuen Testament 303), Tübingen, Mohr Siebeck, 2013Gamble, Harry Y., Livres et lecteurs aux premiers temps du christianisme. Usage et production des textes chrétiens antiques (Christianismes antiques), traduit par P. Renaud- Grosbras [Books and Readers in the Early Church. A History of Early Christian Texts, Yale University, 1995], Genève, Labor et Fides, 2012Pesthy-Simon, Monika, Die Theologie der Versuchung im frühen Christentum (Traditio Christiana. Texte und Kommentare zur patristischen Theologie 15), Bern, Peter Lang, 2011Aragione, Gabriella - Norelli, Enrico (éd.), Des évêques, des écoles et des hérétiques, Actes du Colloque international sur la « Réfutation de toutes les hérésies », Genève, 13-14 juin 2008, Lausanne, Éditions du Zèbre, 2011Heffernan, Thomas J., The Passion of Perpetua and Felicity, Oxford - New York, Oxford University Press, 2012Der Same Seths. Hans-Martin Schenkes Kleine Schriften zu Gnosis, Koptologie und Neuem Testament, Gesine Schenke Robinson - Gesa Schenke - Uwe-Karsten Plisch (éd.) (Nag Hammadi and Manichaean Studies 78), Leyde, Brill, 2012Vita latina Adae et Evae, cura et studio Jean-Pierre Pettorelli, adiuvante et opus perficiente Jean-Daniel Kaestli. Synopsis Vitae Adae et Evae Latine, Graece, Armeniace et Iberice, cura Albert Frey, Jean-Daniel Kaestli, Bernard Outtier et Jean-Pierre Pettorelli (Corpus Christianorum, Series Apocryphorum 18-19), Turnhout, Brepols, 2012Arruzza, Cinzia, Les Mésaventures de la théodicée. Plotin, Origène, Grégoire de Nysse (Nutrix, Studies in Late Antique Medieval and Renaissance Thought - Studi sul pensiero tardoantico medievale e umanistico 6), Brepols, Turnhout, 2011Denzey Lewis, Nicola, Introduction to “Gnosticism”. Ancient Voices, Christian Worlds, New York - Oxford, Oxford University Press, 2013Lahe, Jaan, Gnosis und Judentum : Alttestamentliche und jüdische Motive in der gnostischen Literatur und das Ursprungsproblem der Gnosis (Nag Hammadi and Manichaean Studies 75), Leiden - Boston, Brill, 2012Chiapparini, Guiliano, Valentino gnostico e platonico. Il valentinianesimo della ‘Grande notizia’ di Ireneo di Lione : fra esegesi gnostica e filosofia medioplatonica, preface de Giulia Sfameni Gasparro (Temi metafisici e problemi del pensiero antico. Studi e testi 126), Milan, Vita e Pensiero, 2012Nicola Denzey Lewis, Cosmology and Fate in Gnosticism and Graeco-Roman Antiquity : Under Pitiless Skies (Nag Hammadi and Manichean Studies 81), Leyde, Brill, 2013Popkes, Enno Edzard - Wurst, Gregor (dir.), Judasevangelium und Codex Tchacos (Wissenschaftliche Untersuchungen zum Neuen Testament 297), Tübingen, Mohr Siebeck, 2012Van den Berg, Jacob Albert - Kotzé, Annemaré - Nicklas, Tobias - Scopello, Madeleine (dir.), ‘In Search of Truth’ : Augustine, Manichaeism and other Gnosticism. Studies for Johannes van Oort at Sixty (Nag Hammadi and Manichaean Studies 74), Leyde, Brill, 2010